'Jews of the East': Chinese Migrants in Japanese Discourse on Southward Expansion, 1880–1945. Issue 3 (2nd September 2017) - Tsu, Timothy Y.
ABSTRACT: From the late nineteenth century until the end of the Pacific War, Japanese expansionist discourse urging the country to take on an ever greater role in Southeast Asia had a great impact on how Japanese people imagined their destiny as a nation. That this discourse took Western colonial powers in the region as presumed adversaries is well known, but the fact that it also posited the Chinese diaspora there as a main competitor has received little scholarly attention. This article analyses the growing concern of Japanese southward expansionism since the end of the nineteenth century over Chinese migrants in Southeast Asia. It addresses a gap in existing research on pre-war and wartime Japanese geopolitical and racialist thinking on Southeast Asia. It also presents a wider view on Japanese treatment (or mistreatment) of Chinese in occupied Southeast Asia during World War Two.